The Practice of Using and/or Cutting The Body With Sharp Objects: A Case Study of University Students’ Risk Awareness in Selected Universities in Abia State - E.E.Enwereji,; E, I. Akubugwo; J.O.Onwuka,; D.C.Chikezie, (Journal of Clinical Research In HIV AIDS And Prevention, 2018)
Introduction The practices of having extreme and permanent body modifications as in tattoos and scarifications are gaining popularity among youths especially those in the universities. Not minding the unbearable and painful pressure of sharp objects on the tissues and the risk of being infected with blood transmitted infections including HIV, youths still engage in these practices. This study aimed to examine the extent to which university students are aware of the risks of  using  improperly sterilized and disinfected sharp objects. Materials and Method First year students in three universities, Federal, State and Private Universities were used for the study. A random sample of ninety (90) students made up of 30 students from each of the three universities studied was used.   Drama was used as an intervention that will create awareness on  risks of  utilizing  sharp objects in making  scarifications. The completed copies of self-administered pre- and post-drama  questionnaire    were collected and analyzed quantitatively using Tables and percentages. Results Results  showed that    a  good number of   students 29 (97%) in Michael Okpara University of Agriculture (MOUA) ,  28(93%) in Abia State University (ABSU)  and   27( 90%) in  Rhema University  viewed   sharing sharp objects like razor blades and  syringes  as  risk to blood transmitted infections  especially HIV.  A total of   28(31%) of students both males and females in MOUA,   ABSU, and Rhema had marks (scarification and/ or tattoos) on the  body.  The main reason for having the marks was for traditional identification and this was more among students in MOUA than in others.   Conclusion Based on the  results  of the study, drama proved to be a valuable and timely intervention strategy that created awareness among university students on the risks of using sharp objects to make marks on the body.
Keywords: drama; sharp objects; HIV; blood transmitted infections; malaria